2018
DOI: 10.1002/srin.201800173
|View full text |Cite
|
Sign up to set email alerts
|

Fluid Flow and Heat Transfer in a Tundish with Channel Type Induction Heating

Abstract: Because of the high heating efficiency, channel type induction heating is utilized in the tundish in order to reduce the temperature fluctuations of the molten steel in the process of continuous casting. In order to have a deep insight into the complex MHD (magneto hydrodynamic) process in the tundish with channel type induction heating, water model and mathematical model are performed to describe the fluid flow and the heat transfer in the tundish. A non-isothermal water model with channel heater is built to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 14 publications
0
27
0
Order By: Relevance
“…2. Part I is about the electromagnetic field, 24) part II is about the flow field and temperature field, 25) and part III is about the collision and coalescence among the inclusions in molten steel. The calculation procedure is as follows.…”
Section: Calculation Model and Proceduresmentioning
confidence: 99%
See 3 more Smart Citations
“…2. Part I is about the electromagnetic field, 24) part II is about the flow field and temperature field, 25) and part III is about the collision and coalescence among the inclusions in molten steel. The calculation procedure is as follows.…”
Section: Calculation Model and Proceduresmentioning
confidence: 99%
“…It need no repetition in here. 24,25) In the mathematical model, Joule heating (σ J 2 ) acts as the source term in the energy equation, it increases the temperature of molten steel in the tundish, and related the thermal buoyancy (β (T 0 − T) ρ f g) change the fluid flow. The electromagnetic force (J B)   × acts the source term in the momentum conservation equation, it stirs the molten steel in the tundish.…”
Section: Mathematical Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…They found that there was a significant effect of electromagnetic force on the molten steel flow in the tundish, and that the flow pattern varied with Joule heating, while the electromagnetic force had little effect on it. Yang et al [10,11] established physical and mathematical models to investigate electromagnetic phenomena, flow field, and heat transfer in a channel type induction heating tundish. Results showed that in the induction heating channels, the electromagnetic field, current field, electromagnetic force, and heating power are the greatest.…”
Section: Introductionmentioning
confidence: 99%